Striking First Preemptive and Preventive Attack in U.S. National Security Policy - Mueller, Karl P. (RAND Corporation, 2006)
RAND Project AIR FORCE studied the post-9/11 shift in U.S. defense policy emphasis toward preemptive and preventive attack, asking under what conditions preemptive or preventive attack is worth considering as a response to perceived threats. It considered the role such first-strike strategies are likely to play in future U.S. national security policy. Finally, it identified implications these conclusions have for military planners and policymakers as they prepare to deal with national security threats in the next decade.